Pengembangan ekonomi desa penghasil kopi melalui pemanfaatan ilmu pengetahuan dan teknologi di Kabupaten Belu - Rachmini Saparita; Elok Wahju Hidajat; Eki Karsani Apriliyadi (Riau Journal of Empowerment, 2019)
The research aimed to develop coffee-producing villages economic in Belu District through the use of science and technology in community. Various parties (R & D institutions, central and regional governments and villages) participated synergycally in increasing institutional capacity of farmer groups and BUMDes, introducting science and technology utilization, guiding as well as providing production and marketing facilities, equipment for processing coffee commodities (upstream and downstream), providing facilities and infrastructure to access and support agricultural production. Those interventions are expected could transforme coffee-producing village condition from lag behind to become developing villages.